Saneamento ambiental: uma deficiência na Ilha do Ouro no semi-árido de Sergipe - Neri, Gilson Luiz Teixeira (2005)
This paper presents a study of deficiencies in sanitation ambient`s evaluation at Ilha do Ouro village, city of Porto da Folha, located at Sergipe’s semi-arid, 196km away from the northwest of its capital, Aracaju. It has an approach population of 711 people who inhabits the edge side of São Francisco river. The socioeconomics and ambient conditions the in the place are adverse with the great part of its inhabitants living under subsistence condition, culture farming short duration cycle subjected to the climate’s irregularity which influences the quality of life, when 85% of the family has income of until one minimum wage, that is reflected in the lack on health appearing diseases of poverty and the children in state of malnutrition. The lack of jobs, the low level of schooling and the long period without rains, makes the population depend on government’s social programs. The habitation conditions are precarious and a great part of residential units present an inadequate distribution of rooms with living room, bedroom, kitchen and bathroom, with bad illumination and ventilation, which connect themselves through long halls. These habitations are deficient on basic sanitation and the water consumed is out of drinkable patterns, the trash is collected by municipal agency, although on an irregular way with inadequate disposition, which threats the environment and the domestic sewer that is thrown up to the open air to yards or leaded to the septic tank which are built in flats grounds making harder the infiltration of liquid part in subsoil, causing the overflow to surface and contributing to the domestic and public environment contamination and sprouting of diseases vectors. Most of the population is conscientious about the importance of sanitation in other to have salubrious environment and they identify the problems and detach the positive points, partnership and actions to improve their condition of life and of natural environment and social in according to the results obtained in questionnaires, interviews and answers of the fast participative diagnosis, applied with the help of the public intuition and civil segments answers given by the population.